1993
DOI: 10.1073/pnas.90.8.3383
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in interleukin 2-induced corticotropin-releasing factor release from incubated hypothalami.

Abstract: Stimulation of corticotropin-releasing factor (CRF) release from the hypothalamus by interleukin 2 (IL-2) was recently demonstrated. Cytokines induce nitric oxide synthase (NOS), an enzyme that converts L-arginine into L-citrulline and nitric oxide (NO). NO is believed to be responsible for the cytotoxic action of these agents. The constitutive form of NOS occurs in neurons in the central nervous system and NO appears to play a neurotransmitter role in cerebeilar and hippocampal function. We explored the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(86 citation statements)
references
References 18 publications
5
79
1
1
Order By: Relevance
“…This pattern of IL-1␤ and iNOS induction first in areas without an effective blood-brain barrier and later within brain parenchyma shows a temporal course by which endotoxin-induced inflammation can affect key functions of the brain. In addition to the direct effects of IL-1␤ on brain functions such as temperature regulation, food intake, sleep, and neuroendocrine regulation, IL-1␤ can further modulate CNS functions during inflammation through IL-1␤-induced iNOS, resulting in high levels of NO production that, for example, modulates release of corticotropin-releasing hormone (6,31). We also showed IL-1ra and IL-10 gene expression in the brain during these experiments.…”
Section: Discussionmentioning
confidence: 60%
“…This pattern of IL-1␤ and iNOS induction first in areas without an effective blood-brain barrier and later within brain parenchyma shows a temporal course by which endotoxin-induced inflammation can affect key functions of the brain. In addition to the direct effects of IL-1␤ on brain functions such as temperature regulation, food intake, sleep, and neuroendocrine regulation, IL-1␤ can further modulate CNS functions during inflammation through IL-1␤-induced iNOS, resulting in high levels of NO production that, for example, modulates release of corticotropin-releasing hormone (6,31). We also showed IL-1ra and IL-10 gene expression in the brain during these experiments.…”
Section: Discussionmentioning
confidence: 60%
“…Both the constitutive and inducible form of cyclo-oxygenase are found in endothelial cells, fibroblasts and macrophages after treatment with proinflammatory agents, such as endotoxin (Salvemini et al, 1993;Swierkosz et al, 1995). Other studies have shown that NO activates cyclooxygenase in the hypothalamus, leading to corticotrophin-releasing factor release (Karanth et al, 1993). NO increases arachidonic acid-stimulated PGE2 production in fibroblasts (Salvemini et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…For example, NO appears to mediate via activation of cyclooxygenase the cholinergic and the interleukin-2-induced stimulation of corticotropin-releasing factor release which is mediated by cholinergic neurons within the hypothalamus (22). On the other hand, growth hormone-releasing factor-induced somatostatin release via NO appears to be induced by activation of the guanylate cyclase pathway (23).…”
Section: Resultsmentioning
confidence: 99%